Epothilone B Benefits Nigral Dopaminergic Neurons by Attenuating Microglia Activation in the 6-Hydroxydopamine Lesion Mouse Model of Parkinson’s Disease - Yu, Zhongyuan; Yang, Ling; Yang, Yang; Chen, Siyu; Sun, Dayu; Xu, Haiwei; Fan, Xiaotang (Frontiers in Cellular Neuroscience, 2018)
Parkinson's disease (PD) is characterized by loss of dopamine (DA) neurons in the substantia nigra pars compacta (SNc) and a subsequent reduction in striatal DA levels. Recent studies have shown that systemic administration of subtoxic doses of epothilone B (EpoB), a microtubule stabilizing agent, enhances axonal regeneration. However, the underlying alterations in cellular  mechanisms remain undetermined. In the present study, we investigated the neuroprotective effects of EpoB on DA neurons in mouse model of PD induced by 6-hydroxydopamine (6-OHDA) and in vitro. The results indicated that EpoB improved behavioral deficits, protected the nigrostriatal dopaminergic projections and restored DA level in the striatum of mice exposed to 6-OHDA. Meanwhile, EpoB attenuated microglia activation in the SNc of PD mice. Furthermore, EpoB treatment ameliorated the cytotoxicity to MN9D dopaminergic cells in a microglia-conditioned cultured media system, and redistributed the cytoskeleton of microglial BV2 and caused the morphological transition, inhibited the polarization to the M1 phenotype by suppressing lipopolysaccharide (LPS)-induced expression of pro-inflammatory factors including interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α. Overall, our study suggested that EpoB treatment protects nigral DA neurons and projections through limiting the cytotoxicity of activated microglia in 6-OHDA lesioned mice.